Technical risk management: the case of a software development company - Penha, Renato; Kniess, Claudia Terezinha; Bergman, Daniel Reed; Biancolino, Cesar Augusto (Revista de Administração da UFSM, 2016)
Failures in project management translate into deviations in scope, within or cost affecting the profitability and feasibility of projects. This article aims to analyze the contribution of the management of technical risks in completing projects in a software development environment. Through a qualitative and quantitative analysis of a study conducted in a Brazilian company inserted in the information technology market, it was possible to identify factors that contributed to the reduction in the rate of deviation of time for completion of projects. The results indicate that after the adoption of techniques for managing technical risks, the company increased the percentage of projects delivered within 58.71% in 2005 to 70.70% in 2012 was possible to present a significant reduction in delays and cancellations projects from the new policies.